2000
DOI: 10.1097/00005053-200001000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Research on Religious Variables in Five Major Adolescent Research Journals: 1992 to 1996.

Abstract: A review of quantitative research studies published between 1992 and 1996 in five major adolescent journals revealed that 11.8% (109 of 922) included a measure of religion. This percentage (11.8%) is 3 to 10 times higher than that found in previous reviews of empirical research in psychological and psychiatric journals, suggesting that adolescent research journals are more sensitive to the role of religious factors on mental health than research in related disciplines. The results are discussed in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…A review of quantitative studies published between 1992 and 1996 in five major adolescent research journals found that 11.8% of the articles included a measure of religion-a percentage 3 to 10 times higher than found in broader journal searches (Weaver et al, 2000).…”
Section: A Poorly Understood Human Capacitymentioning
confidence: 95%
“…A review of quantitative studies published between 1992 and 1996 in five major adolescent research journals found that 11.8% of the articles included a measure of religion-a percentage 3 to 10 times higher than found in broader journal searches (Weaver et al, 2000).…”
Section: A Poorly Understood Human Capacitymentioning
confidence: 95%
“…The meaning of life and death, of relationships to God, the universe, to oneself and to other people, certainly determine how an individual will respond to personal crises” (p. 108). Religion/spirituality is a complex and multifaceted construct which requires measures that reflect its complexity and multidimensionality. Using a single variable (often consisting of “church affiliation”) may provide insufficient information (Larson et al, 1986 cited in Weaver, Samford, Morgan, Lichton, Larson, & Garbarino, 2000). The work by Kendler, Liu, Gardner, McCullough, Larson, and Prescott (2003) offers a good example of a multidimensional approach to the study of religiosity.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…Additional studies have shown church attendance and an adolescent’s religious beliefs as protective against voluntary sexual activity (Holder et al, 2000; Langille & Curtis, 2002; Levin et al, 2001; McCree, Wingood, DiClemente, Davies, & Harrington, 2003), and other high-risk behaviors such as school absenteeism, delinquency, poor body image, disordered eating, antisocial behavior and suicidal involvement (Hyde, 1990; Resnick, Harris, & Blum, 1993; Weaver et al, 2000). …”
Section: 1 Introductionmentioning
confidence: 99%